2016
DOI: 10.1111/cen.12980
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity associated with metreleptin treatment in patients with obesity or lipodystrophy

Abstract: Summary Objective Recombinant human leptin (metreleptin) improves glycemia and hypertriglyceridemia in patients with generalized lipodystrophy; antibody development with in vitro neutralizing activity has been reported. We aimed to characterize anti-metreleptin antibody development, including in vitro neutralizing activity. Design Two randomized controlled studies in patients with obesity (twice-daily metreleptin ± pramlintide for 20–52 weeks; 2006–2009); two long-term, open-label studies in patients with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 26 publications
2
39
0
3
Order By: Relevance
“…In vivo neutralizing antibody activity to leptin has been reported (58, 59). The clinical implications remain unclear, but may include treatment failure and sepsis (59).…”
Section: Treatment Of Lipodystrophy Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo neutralizing antibody activity to leptin has been reported (58, 59). The clinical implications remain unclear, but may include treatment failure and sepsis (59).…”
Section: Treatment Of Lipodystrophy Syndromesmentioning
confidence: 99%
“…The clinical implications remain unclear, but may include treatment failure and sepsis (59). Additional serious adverse events occurring during metreleptin treatment are likely related to the underlying lipodystrophy syndrome, rather than metreleptin.…”
Section: Treatment Of Lipodystrophy Syndromesmentioning
confidence: 99%
“…As one example for key areas warranting intense future studies, major efforts will be necessary to understand how cell types such as tanycytes, microglia and astrocytes interact with neurons to meaningfully integrate existing knowledge of leptin biology with neuroendocrine pathologies resulting from-and driving-metabolic disease. Importantly, for leptin to (re)enter clinical studies as anti-obesity therapy, previously reported adverse effects associated with leptin administration, including hypertension and immunogenicity, will have to be carefully assessed [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Weiterhin wurde das Vorkommen einer neutralisierenden Antikörperaktivi-tät gegen Leptin berichtet [62,63]. Die klinische Bedeutung dieses Befundes ist noch unklar.…”
Section: Nebenwirkungen Einer Metreleptin-therapieunclassified
“…Die klinische Bedeutung dieses Befundes ist noch unklar. Ein mangelndes Ansprechen auf die Behandlung sowie das Auftreten einer Sepsis können Folgen davon sein [63].…”
Section: Nebenwirkungen Einer Metreleptin-therapieunclassified